Vinzenz Bronzin<U+0019>s Option Pricing Models Exposition and Appraisal - Hafner, Wolfgang.; Zimmermann, Heinz. (Springer Berlin Heidelberg, 2009)
In 1908, Vinzenz Bronzin, a professor of mathematics at the Accademia di Commercio e Nautica in Trieste, published a booklet in German entitled Theorie der Prm̃iengeschf̃te (Theory of Premium Contracts) which is an old type of option contract. Almost like Bachelier<U+0019>s now famous dissertation (1900), the work seems to have been forgotten shortly after it was published. However, almost every element of modern option pricing can be found in Bronzin<U+0019>s book. He derives option prices for an illustrative set of distributions, including the Normal. - This volume includes a reprint of the original German text, a translation, as well as an appreciation of Bronzin's work from various perspectives (economics, history of finance, sociology, economic history) including some details about the professional life and circumstances of the author. The book brings Bronzin's early work to light again and adds an almost forgotten piece of research to the theory of option pricing.